PERANCANGAN DAN PEMBUATAN UNDERSHOT WATERWHEEL SEBAGAI PENGGERAK SPIRAL PUMP UNTUK IRIGASI PERTANIAN - Rochmad Eko; Agung Fauzi Hanafi; I. G. N. A. Satria Prasetya D.Y.; Enggar Priyadi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
Lack of water is one of the problems in the agricultural sector. The location of the farm which is located above the water source causes difficulties in flowing the rice field area. During the dry season, farmers are forced to lift water using a water pump. Therefore, a more economical water pump is needed, one of that is a spiral pump which is driven by an undershot waterwheel. The results of the undershot waterwheel design obtained a diameter of 1 m, a width of 1.15 m, and a blade area of 0.459 m2. The frame of the wheel is made of plain concrete iron with a diameter of 8 mm, the blade of the wheel is made of 0.4 mm thick galvanized plate, the support for the pinwheel is made of angled iron with a size of 4 x 4 cm, while the shaft of the pinwheel is made of galvanized pipe with an outer diameter of 33.8 mm and 3.2 mm thick. From the test results, the wheel rotation is 15.2 rpm, torque is 9.5 Nm, wheel power is 15.11 watts, and the undershot waterwheel efficiency is 16.54%.